Design and performance analysis of VCO for standard GSM using MEMS - Al-Khateeb, Khalid A. Saeed; Al-Khateeb, Wajdi Fawzi Mohammed (IIUM Press, 2010)
The design of a prototype monolithic Micro Electro-Mechanical Systems (MEMS) electronic circuits, namely the Voltage Controlled Oscillators (VCOs) is presented. The components can achieve the stringent requirements of wireless communication applications such as GSM cellular telephony. The VCO meets the low phase noise specifications of -136 dBc/Hz at large offset frequency of 3MHz, over the appropriate frequency range. The model of the monolithic VCO is based on the topology of the Colpitts Oscillator. It is relatively less complicated, which facilitates the practical integration of the MEMS components into the configuration. The variable capacitor and the monolithic 3-D coil inductor are suitable for low phase-noise and low power consumption at the application frequencies. A PSpice simulation model was developed with MEMS switching devices that can be integrated into the system. The model helps in determining the design parameters, which affect the performance and operation reliability of the RF transceiver system, for which a prototype has been tested and proved successful.